Figurative Language Analysis in Animated Film Kung Fu Panda 3 - Mukhsin, Hasna Nurain; Tawakkal, Afifah Ibna Fatina (Journal of English Language Teaching, Linguistics, and Literature Studies, 2024)
Figurative Language Analysis in Animated Film Kung Fu Panda 3. Figurative language enriches the dialogue of animated films, adding depth and meaning. This study aims to analyze the figurative language used in the animated film Kung Fu Panda 3 produced by DreamWorks Animation. This study utilized the figurative language theory by Herbert L. Colston. This study used descriptive qualitative method to analyze the dialogues from various scenes containing figurative language. The data collection steps are as follows: First, the researcher reads the transcript while watching Kung Fu Panda 3 and marks figurative language. Second, the researcher identifies and groups types of figurative language based on Colston's theory. Finally, the context and meaning of each figurative language is explained and analyzed. As the result, metaphors are the most frequently used type of figurative language in this film. Through figurative language, the speakers express several meaningful messages about the importance of cultivating self-confidence, particularly in understanding and accepting ourselves.Keyword: Figurative Language, metaphor, messages